KEMANDIRIANÂ ANAKÂ KELOMPOKÂ AÂ TAMANÂ KANAKâ€KANAKÂ MANDIRIÂ DESAÂ SUMBERÂ ASRIÂ KECAMATANÂ NGLEGOKÂ KABUPATENÂ BLITARÂ - saida, naili (Universitas Muhammadiyah Surabaya, 2016)
ThisÂ studyÂ aimsÂ toÂ describeÂ theÂ child'sÂ independenceÂ inÂ groupÂ AÂ ofÂ Mandiri kindergartenÂ Blitar.Â ThisÂ studyÂ usesÂ descriptiveÂ qualitativeÂ research.Â HisÂ researchÂ interests areÂ asÂ manyÂ asÂ 10Â childrenÂ inÂ groupÂ AÂ ofÂ MandiriÂ kindergarten.Â TheÂ dataÂ analysis techniqueÂ consistedÂ ofÂ qualitativeÂ dataÂ analysisÂ andÂ descriptive.Â QualitativeÂ dataÂ analysis usingÂ theÂ techniquesÂ accordingÂ toÂ MilesÂ andÂ HubermanÂ consistingÂ ofÂ dataÂ reduction,Â data display,Â andÂ verificationÂ collectedÂ throughÂ independenceÂ instruments,Â interviews,Â field notes,Â andÂ documentation.Â FromÂ thisÂ researchÂ itÂ isÂ knownÂ thatÂ theÂ independenceÂ of childrenÂ inÂ groupÂ AÂ MandiriÂ kindergarten implantedÂ throughÂ intervention,Â habituationÂ and reinforcement. Â Keywords:Â Independence,Â groupÂ AÂ ofÂ MandiriÂ Kindergarten